TEORETHICAL EVALUATION OF ANTHROPOGENIC RISKS IN TAZLAU RIVER BASIN - LUMINITA BIBIRE; MIHAELA-BEATRICE BARBIERU; NARCIS BARSAN; ADRIAN STELIAN GHENADI (Journal of Engineering Studies and Research)
In the Tazlau Basin there was a really strong anthropogenic impact. Many areas have almost totally been deforested, the grazing and agriculture have extensively and irrational been practiced, underground reserves have been exploited, too etc. The expanding of settlements along the rivers and building of modern communication routes along beds favored the phenomena of flooding and destruction of hydraulic works. These all aspects led to frequent occurrence of risk events: erosions, landslides, degradation of the rivers beds, pollution of air, water, vegetation, soil, etc. The paper identifies anthropogenic risk factors from Tazlau Basin, and proposes analyzes of the consequences and the measures to avoid these ensuing consequences.